LABORATORY STUDY OF POLYMERIZATION DEPTH OF COMPOSITE MATERIALS - O.A. Udod; Kh.I. Bekuzarova (Ukrainian Medical Stomatological Academy, 2018)
With the advent of modern improved restorative materials, the process of teeth restoration has become even more complex, but it provides an impeccable anatomical, functional and aesthetic result. In the new generation of composites there is a number of advantages, namely, increased mechanical strength, increased abrasion resistance, hardness, colour stability. All these allows restoring the anatomical shape of teeth and functional characteristics even with a significant degree of damage. However, after restoration, complications are often associated with polymerization of stress and shrinkage of composite materials, inconsistency between the coefficients of volume expansion of materials and hard tissues of teeth, etc. Recently, due to the improvement of materials, the appearance of highly filled composites, it has become possible to apply the first layer of reinforced rarefaction of composite with a thickness of up to 4 mm. However, when the thickness of a layer of any composite material increases, there must be a question about the degree, quality and depth of the polymerization that initiates the light flux of the photopolymerizer. Therefore, the choice of materials and technology for restoration of the teeth should be reasonable and optimal. The aim of this work was to study the polymerization depth of composite materials under different modes of light exposure in laboratory conditions. Materials and methods. In the course of a laboratory research the ISO 4049 method was used, the depth of polymerization of liquid and composite materials, and total number of 120 samples were studied. Samples were made up in a special shape with a diameter of 4 mm hole and exposed to light flux of 1000 mW/cm2 of LED photopolymerizer in two modes: "soft start" and constant high intensity. Then a sample of photoconductive material was extracted from the form, a layer of material that was not hardened was separated, the length of the hardened specimen was measured, divided by 2 and the value for the polymerization depth of the material under study was obtained. Results of the research and their discussion. Statistically significant maximum indices of the polymerization depth were obtained with the use of composite materials for solidification of the light flux of a photoconductive photoconductor of constant high intensity. Light flux in the "soft start" mode leads to a systematic decrease in the level of polymerization depth. But if we compare the polymerization depth of samples of nanocomposite material in case of one-stage hardening with the adhesive system, they were close enough to such relatively rarefying composites in both modes of light exposure. Conclusions. The results obtained in the study indicate the expediency, in case of need, to increase the thickness of the layer of rarefied composite materials for the application of their solidification of the light flux of constant high intensity. Concerning the simultaneous hardening of nanocomposite material and the adhesive system, it can be assumed from the results of the study that some of the properties of this material, thus obtained, correspond to the corresponding characteristics of the rarefied composites.